Analisa Organoleptik Produk Es Krim Kedelai Hitam Dengan Penambahan Lidah Buaya - Eka Sari, Afrinia; Eka Nur Oktantia, Dela; Kusumowati, Dwi; Dhanisa Minati, Shafiah (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
Ice cream is a dairy product that is based on milk and has a high fat and protein content, but low in fiber. Therefore, in this study, black soybeans and aloe vera were added as a source of fiber. This study used an experimental descriptive design using 3 formulas with differences in the addition of aloe vera, namely F1 (3 g), F2 (5 g) and F3 (7 g), where the test conducted in this study was an organoleptic test using 35 panelists. The results of the Anova test for the third hedonic test of the formula obtained the results of No Real Difference, where all three formulas were favored by panelists. From this study, it is expected that there will be further tests related to fiber analysis in black soybean ice cream and aloe vera.